2015
DOI: 10.1186/s13046-015-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

CMTM4 is frequently downregulated and functions as a tumour suppressor in clear cell renal cell carcinoma

Abstract: BackgroundChemokine-like factor (CKLF)-like MARVEL transmembrane domain-containing family (CMTM) is a gene family involved in multiple malignancies. CMTM4 is a member of this family and is located at chromosome 16q22.1, a locus that harbours a number of tumour suppressor genes. It has been defined as a regulator of cell cycle and division in HeLa cells; however, its roles in tumourigenesis remain poorly studied.MethodsAn integrated bioinformatics analysis based on the array data from the GEO database was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…To our knowledge, this is one of the first in vivo studies comparing the differences in gene and pathway expression in RT naïve HNC vs recurrent previously irradiated HNC samples. Our study identified a differential expression of various genes, with previously described associations with HNC stem cells, proliferation, and radioresistance . Most notably, our post‐RT samples had a significant downregulation of the Wnt and Myc pathways.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…To our knowledge, this is one of the first in vivo studies comparing the differences in gene and pathway expression in RT naïve HNC vs recurrent previously irradiated HNC samples. Our study identified a differential expression of various genes, with previously described associations with HNC stem cells, proliferation, and radioresistance . Most notably, our post‐RT samples had a significant downregulation of the Wnt and Myc pathways.…”
Section: Discussionsupporting
confidence: 75%
“…CMTM4 is a tumor suppressor gene characterized by G2/M phase regulation, p21 upregulation, and inhibition of cell migration . The downregulation of CMTM4 has been described in clear cell renal cell carcinoma, with restoration of expression significantly suppressing cell growth in vitro and in xenograft models . Our study suggests that the decreased expression of these tumor suppressor genes may play a larger role in the carcinogenesis and progression of RT naive tumors, but may have a limited role in the growth of recurrent previously irradiated HNC.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Assessment of cell proliferation was done at AE (20, 40, 60, 80, 100 lM) with an optical density of 450 nm. 27 Triplicate wells were performed in each assay, and the assay was replicated at least four times.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Therefore, it is extremely important for us to further explore the molecular mechanisms of this deadly disease. Identification of novel genes that are potentially recognized as diagnostic and prognostic biomarkers and functionally involved in the ccRCC tumorigenic initiation and progression may improve early diagnosis of ccRCC and further help to develop more strategies for ccRCC treatment 6.…”
Section: Introductionmentioning
confidence: 99%